Continuity and Change in the (New) Kosciuszko Foundation Dictionary - Adamska-Sałaciak, Arleta (Studia Anglica Posnaniensia, 2016)
The Kościuszko Foundation Dictionary (KFD)1, the only bilingual dictionary between Polish and American English, first came out in 1959 (English-Polish volume) and 1961 (Polish-English volume). Between then and 1995, it was reprinted fourteen times, with the content completely intact. In 2003, The New Kosciuszko Foundation Dictionary (NKFD1) finally appeared, in two printed volumes accompanied by a CD. Originally intended as a straightforward update of KFD, it ended up being closer to a brand new dictionary, linked with its predecessor mainly through the title - a consequence of the continuing patronage of The Kosciuszko Foundation - and through its focus on American English. With around 133,000 main entries, it was, at the time of publication, the most comprehensive English-Polish, Polish-English dictionary in existence. A new, revised and enlarged edition (NKFD2) is about to be published soon, this time exclusively in digital form. Having been involved in the latter two projects - respectively, as editor of the English-Polish volume and editor-in-chief - the author examines the development of the dictionary, tracing the continuity and change in its three successive incarnations.